Cellular FLICE-inhibitory protein splice variants inhibit different steps of caspase-8 activation at the CD95 death-inducing signaling complex* - Krueger, Andreas; Krammer, Peter H. (The journal of biological chemistry, 2001)
Upon stimulation, CD95 (APO-1/Fas) recruits the adapter molecule FADD/MORT1, procaspase-8, and the cellular FLICE-inhibitory proteins (c-FLIP) into the death-inducing signaling complex (DISC). According to the induced proximity model, procaspase-8 is activated in the DISC in an autoproteolytic manner by two subsequent cleavage steps. c-FLIP proteins exist as a long (c-FLIPL) and a short (c-FLIPS) splice variant, both of them capable of protecting cells from death receptor-mediated apoptosis. In stably transfected BJAB cells, both c-FLIPS and c-FLIPL block procaspase-8 activation at the DISC. However, cleavage is blocked at different steps. c-FLIPL allows the first cleavage step of procaspase-8, leading to the generation of the p10 subunit. In contrast, c-FLIPS completely inhibits cleavage of procaspase-8. Interestingly, p43-c-FLIPL lacking the p12 subunit also prevents cleavage of procaspase-8. In contrast, a nonprocessable mutant of c-FLIPL allows the first cleavage of procaspase-8. In conclusion, both c-FLIP proteins prevent caspase-8 activation at different levels of procaspase-8 processing at the DISC. Our results indicate that c-FLIPL induces a conformation of procaspase-8 that allows partial but not complete proteolytical processing, whereas in contrast c-FLIPS even prevents partial procaspase-8 activation at the DISC.
Elektronische Reproduktion der Druck-Ausgabe
Available online 4 January 2021
Gesehen am 26.04.2021